2014
DOI: 10.1136/sextrans-2014-051531
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility ofChlamydia trachomatisscreening and treatment in pregnant women in Lima, Peru: a prospective study in two large urban hospitals: Table 1

Abstract: Objectives Chlamydia trachomatis, which is asymptomatic in most women, causes significant adverse effects for pregnant women and neonates. No programmes conduct antenatal screening in Latin America. We determined chlamydia prevalence, the feasibility and acceptability of chlamydia screening, and adherence to treatment in pregnant women in two urban public hospitals in Lima, Peru. Methods We offered chlamydia screening using self-collected vaginal swabs to pregnant women ≥ 16 years during their first antenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 7 publications
3
19
0
1
Order By: Relevance
“…8 A more recent study, reported that 88% of pregnant women had a negative chlamydia NAAT 21 days following single-dose therapy, which is consistent with our data. 10 Our recommended timing for test-of-cure may decrease unnecessary retreatment of noninfectious organisms detected by NAAT before 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A more recent study, reported that 88% of pregnant women had a negative chlamydia NAAT 21 days following single-dose therapy, which is consistent with our data. 10 Our recommended timing for test-of-cure may decrease unnecessary retreatment of noninfectious organisms detected by NAAT before 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not address why six women continued to have a positive NAAT despite effective therapy. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Los valores de prevalencia comunicados en la población adolescente general fue del 8,7 % en Córdoba Capital (14) y del 3,5% en los ingresantes universitarios en la ciudad de Bahía Blanca, Buenos Aires (15) . En América Latina, se han reportado prevalencias en embarazadas del 5,9% en Chile (16) , 10% en Lima, Perú (17) y 12,3% en el sur de Brasil (18) . En Buenos Aires, se reportó en el año 2001 una prevalencia del 2,5% en mujeres asistidas en un hospital de esa provincia; este grupo de estudio incluyó sólo pacientes sintomáticas (19) .…”
Section: Introductionunclassified
“…As part of a larger study to determine the acceptability and feasibility of Chlamydia trachomatis screening among pregnant women in Lima, Peru, we found a prevalence of Chlamydia trachomatis of 10% 12 . The primary objectives of the substudy were to report partner treatment uptake and to examine the associations between partner treatment uptake and whether the women were living with their partners.…”
mentioning
confidence: 90%